The use of cognitive reconstruction strategies with self-assessment (CRSA) in writing AI-based scientific papers in Indonesian language education learning - Restapaty, Ratna; Harsiati, Titik; Zahro, Azizahtuz (Faculty of Languages, Arts, and Culture Universitas Negeri Yogyakarta, 2026)
The ability to recognize, appreciate, and connect different elements to resolve different issues is important for cognitive development and acquiring the different dimensions of the Indonesian language. Thus, it is imperative to study different cognitive approaches in understanding different and diverse scientific documents, particularly through the AI-based Cognitive Reconstruction Self-Assessment (CRSA) tool. This study, in the sphere of Indonesian Language Education, aims to study the degree to which the integration of chatbot with CRSA, improves the comprehension of students. The study found the cognitive scaffolding influenced by artificial intelligence promotes reading, understanding concepts, and better pedagogical interventions. This, in addition to helping students understand the structure of scientific writing, improves critical thinking. Moreover, the CRSA framework offers the opportunity to better organize, refine and improve the personalization of educational processes. The ability of artificial intelligence to personalize educational processes is paramount. Overall, the combination of CRSA and AI will inevitably help meet the contemporary educational challenges, particularly personalization and flexibility, and improve the practice of teaching.